Comparison of ABI, TBI, TOE Pressure, and Ankle Pressure Examinations in PAD Patients, Before and After Angioplasty with and without Type 2 DM at RSCM - Rizki, Mohammad Nazril; Suhartono, Raden; Herqutanto , Herqutanto (Jurnal Locus Penelitian dan Pengabdian, 2025)
Diabetes Mellitus (DM) exacerbates peripheral artery disease (PAD) and can affect the diagnostic accuracy of the ankle-brachial index (ABI) due to arterial calcification. Alternative examinations such as toe-brachial index (TBI), toe pressure (TP), and ankle pressure (AP) require evaluation to compare their effectiveness post-angioplasty in PAD patients with and without DM. This study aims to compare the changes in the values of these four parameters before and after angioplasty in both groups of patients. Method. This retrospective cohort study involved 78 PAD patients (39 with DM, 39 without DM) at Cipto Mangunkusumo Hospital. Hemodynamic parameters (ABI, TBI, AP, TP) were measured 24 hours before and after angioplasty. Bivariate analysis and linear regression are used to assess changes and their predictive factors. Post-angioplasty, all parameters showed significant improvement in both groups. However, the delta differences between groups were only significant in ABI and AP, not in TBI and TP. Preangioplasty parameter values were the main predictors of the magnitude of post-operative changes (p<0.001), while age had only a significant effect on delta TBI and TP. Conclusion. Angioplasty significantly improved ABI, TBI, TP, and AP values in PAD patients with and without type 2 DM. There was a significant difference between the delta parameters of ABI and AP in both groups after angioplasty. The value of the clinical parameters of preangioplasty had an effect on the delta value of each parameter, while age only affected the change in TBI and TP. The finding that TBI and TP did not show  significant delta differences  between the DM and non-DM groups implied that these two parameters were more robust and less affected by the condition of diabetes, making them worthy of consideration as a more reliable assessment tool, particularly in diabetic populations at risk of arterial calcification.